Multiphoton scanning laser microscope based on femtosecond fiber laser - Kwaśny, Alicja; Bogusławski, Jakub; Soboń, Grzegorz (Photonics Letters of Poland, 2022)
We present a multiphoton scanning laser microscope based on a femtosecond frequency-doubled erbium-doped fiber laser. The laser used in the epi-illumination microscope setup generated 95 fs pulses at the wavelength of 780 nm with 44.3 mW average power at 100 MHz pulse repetition rate. The imaging process was controlled by custom software developed in the NI LabVIEW environment. Detection of two-photon fluorescence was proven by acquiring a series of images from various biological samples. Full Text: PDF References J.W. Lichtman, J.A. Conchello, "Fluorescence microscopy", Nature methods 2(12), 910 (2005). CrossRef W. Zipfel, R. Williams, W. Webb, "Nonlinear magic: multiphoton microscopy in the biosciences", Nat. Biotechnol. 21, 1369 (2003). CrossRef Coherent, Chameleon Ultra Datasheet (2019). DirectLink J. Boguslawski et al., "In vivo imaging of the human eye using a 2-photon-excited fluorescence scanning laser ophthalmoscope", J. Clin. Invest. 132(2), e154218 (2022). CrossRef M.J. Marzejon et al., "Two-photon microperimetry with picosecond pulses", Biomed. Opt. Expr. 12, 462 (2021). CrossRef A. Fast et al., "Institutional Drivers Influence on CSR Engagement: A Comparison of Developed & Developing Economies", Sci. Rep. 10, 18093 (2020). CrossRef D. Stachowiak et al., "Femtosecond Er-doped fiber laser source tunable from 872 to 1075 nm for two-photon vision studies in humans", Biomed. Opt. Expr. 13, 1899 (2022). CrossRef MenloSystems, T-light Femtosecond Fiber Laser 1560 nm (2013). DirectLink J. Yao, L.V. Wang, "Photoacoustic microscopy", Laser and Photonics Rev. 7, 758 (2013). CrossRef D. Stachowiak et al., "Frequency-doubled femtosecond Er-doped fiber laser for two-photon excited fluorescence imaging", Biomed. Opt. Expr. 11, 4431 (2020). CrossRef B.R. Masters et al., "Mitigating thermal mechanical damage potential during two-photon dermal imaging", J. Biomed. Opt. 9, 1265 (2004). CrossRef